Merancang dan Menerapkan Strategi Arsitektur Merek - Anisa Hasna; Adesty Srimukti (Marketgram Journal, 2023)
Brand is an intangible asset for an organization where the ability to manage the brand becomes an important strategy for the company. This brand architecture strategy is a determinant of how the company gives a picture of what it wants to give to consumers. The choice of brand, new and existing services will be determined by the brand's architectural strategy. In addition, the brand strategy will provide and direct the product roadmap into the future and as a guide where and how to achieve it. It is unlikely that a company can manage and maximize brand equity and value without a brand architecture strategy. To that end, we outline a three-step process for designing and implementing a brand architecture, along with guidelines and insights on brand architecture strategy.